2010
DOI: 10.1097/ncq.0b013e3181ce3ae4
|View full text |Cite
|
Sign up to set email alerts
|

Medication Safety Initiative in Reducing Medication Errors

Abstract: The purpose of the study was to evaluate whether a Medication Pass Time Out initiative was effective and sustainable in reducing medication administration errors. A retrospective descriptive method was used for this research, where a structured Medication Pass Time Out program was implemented following staff and physician education. As a result, the rate of interruptions during the medication administration process decreased from 81% to 0. From the observations at baseline, 6 months, and 1 year after implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 12 publications
5
45
0
2
Order By: Relevance
“…Our results are in accordance with those reported by Hellings et al 14 and the study conducted in Taiwan and China 4 23 28. Meanwhile, a study by Elisa E in a Northern California hospital of the USA showed that the most common causes of medication errors were high workload (25.3%), fatigue or lack of sleep (16.5%) 29. Therefore, it is important for the pharmacy to allocate staff and working hours more adequately to reduce the medication errors and improve patient safety.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with those reported by Hellings et al 14 and the study conducted in Taiwan and China 4 23 28. Meanwhile, a study by Elisa E in a Northern California hospital of the USA showed that the most common causes of medication errors were high workload (25.3%), fatigue or lack of sleep (16.5%) 29. Therefore, it is important for the pharmacy to allocate staff and working hours more adequately to reduce the medication errors and improve patient safety.…”
Section: Discussionsupporting
confidence: 92%
“…Eleven papers met the inclusion criteria (figure 1). 22 26 31–39 Of these, two papers by Nguyen et al 35 36 reported results from the same study with the second paper reporting data from a further follow-up period in addition to the original baseline data. Thus only results from the second paper are presented in the results and tables.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers by Kliger et al 33 34 also presented findings on the same project, but with an extended sample and follow-up data, thus both were included as separate studies. Studies by Kliger et al and Nguyen et al 36 were related to the same broader project, the ‘Integrated Nurse Leadership Program’. Online supplementary table S1 reports details of the studies, including setting, interventions implemented, outcomes and methods of measurement.…”
Section: Resultsmentioning
confidence: 99%
“…25 In the quality improvement project presented here, the project team implemented a set of evidence-based strategies to limit interruptions during scheduled, peak medication administration times in the progressive cardiac care setting. The project team embedded the interruption strategies into practice guidelines to promote communication, coordination of care, and teamwork during medication administration.…”
Section: Introduction To the Progressive Cardiac Care Quality Improvementioning
confidence: 99%